Soccer in times of covid-19: remarks on the contamination of Brazilian soccer players - Jeferson Roberto Rojo; Fernando Augusto Starepravo (Universitas Majalengka, 2022)
This manuscript discusses the contamination and dissemination of COVID-19 within sports competitions. Data related to the number of athletes in the first division of Brazilian soccer were used as a starting point. After the competition was resumed, 302 out of 653 players tested positive for COVID-19. Compared to the rate for the total population of Brazil, that number is extremely high and reveals major differences in implementing preventive measures as well as controlling transmission. This can be explained by differences in financial resources to support protocols in strict ways, or even by the fact that the individual social dynamics of athletes did change despite the new life style imposed by the pandemic.